1997
DOI: 10.1007/bf03168543
|View full text |Cite
|
Sign up to set email alerts
|

Time and flow study results before and after installation of a hospital information system and radiology information system and before clinical use of a picture archiving and communication system

Abstract: The effectiveness of a hospital information system (HIS) and a radiological information system (RIS) was evaluated to optimize preparation for the planned full clinical operation of a picture archiving and communication system (PACS), which is now linked experimentally to the HIS and the RIS. One thousand IC (integrated circuit) cards were used for time studies and flow studies in the hospital. Measurements were performed on image examination order entry, image examination, reporting, and image delivery times.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 8 publications
1
13
0
1
Order By: Relevance
“…These results were statistically significant at 5 %. The earlier study found that the mean TRWT reduced from 26.8 (SD 6.8) to 3.6 (SD 2.5)h following the RIS implementation [129].…”
Section: Radiology Information System (Ris)mentioning
confidence: 89%
See 1 more Smart Citation
“…These results were statistically significant at 5 %. The earlier study found that the mean TRWT reduced from 26.8 (SD 6.8) to 3.6 (SD 2.5)h following the RIS implementation [129].…”
Section: Radiology Information System (Ris)mentioning
confidence: 89%
“…Two (3.5 % of 53) studies investigated the RIS and both used the pre-and post-intervention design. Both studies investigated different components of patient waiting times: the TRWT for orthopaedic patients [129] and the RTAT for MRI and mammography [130]. The results were mixed.…”
Section: Radiology Information System (Ris)mentioning
confidence: 99%
“…51,71,72 Therefore, we expect to observe higher impacts on productivity measures for whole in-scale PACS.…”
Section: Main Evaluation Dimensionsmentioning
confidence: 95%
“…To accomplish the goal of a same day turn-around-time for CD34 + reporting, it was necessary to enlist the good will and efforts of several different clinical and laboratory services, all of which had other service demands. To understand the work flow, a time flow chart [6][7][8][9] was designed to capture the series of events and times from the admission of the patient to the hemapheresis service through reporting of the results back to the hemapheresis attending physician and the patient (Table I). Documentation of work flow and process via the time flow chart led to a realistic understanding of the time constraints and problems faced in achieving same day reporting of CD34 + progenitor cells.…”
Section: Introductionmentioning
confidence: 99%